Randomised controlled cognition trials in remitted patients with mood disorders published between 2015 and 2021: A systematic review by the International Society for Bipolar Disorders Targeting Cognition Task Force. (24th February 2022) - Miskowiak, Kamilla W.; Seeberg, Ida; Jensen, Mette B.; Balanzá‐Martínez, Vicent; del Mar Bonnin, Caterina; Bowie, Christopher R.; Carvalho, Andre F.; Dols, Annemieke; Douglas, Katie; Gallagher, Peter; Hasler, Gregor; Lafer, Beny; et al.
Abstract: Background: Cognitive impairments are an emerging treatment target in mood disorders, but currently there are no evidence‐based pro‐cognitive treatments indicated for patients in remission. With this systematic review of randomised controlled trials (RCTs), the International Society for Bipolar Disorders (ISBD) Targeting Cognition Task force provides an update of the most promising treatments and methodological recommendations. Methods: The review included RCTs of candidate pro‐cognitive interventions in fully or partially remitted patients with major depressive disorder or bipolar disorder. We followed the procedures of the Preferred Reporting Items for Systematic reviews and Meta‐Analysis (PRISMA) 2020 statement. Searches were conducted on PubMed/MEDLINE, PsycInfo, EMBASE and Cochrane Library from January 2015, when two prior systematic reviews were conducted, until February 2021. Two independent authors reviewed the studies with the Revised Cochrane Collaboration's Risk of Bias tool for Randomised trials. Results: We identified 16 RCTs ( N  = 859) investigating cognitive remediation (CR; k  = 6; N  = 311), direct current or repetitive magnetic stimulation ( k  = 3; N  = 127), or pharmacological interventions ( k  = 7; N  = 421). CR showed most consistent cognitive benefits, with two trials showing improvements on primary outcomes. Neuromodulatory interventions revealed no clear efficacy. Among pharmacological interventions, modafinil and lurasidone showed early positive results. Sources of bias included small samples, lack of pre‐screening for objective cognitive impairment, no primary outcome and no information on allocation sequence masking. Conclusions: Evidence for pro‐cognitive treatments in mood disorders is emerging. Recommendations are to increase sample sizes, pre‐screen for impairment in targeted domain(s), select one primary outcome, aid transfer to real‐world functioning, investigate multimodal interventions and include neuroimaging.